2016
DOI: 10.1016/j.cbpa.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of dietary polyunsaturated fatty acids and parasite exposure on eicosanoid-related gene expression in an invertebrate model

Abstract: Eicosanoids derive from essential polyunsaturated fatty acids (PUFA) and play crucial roles in immunity, development, and reproduction. However, potential links between dietary PUFA supply and eicosanoid biosynthesis are poorly understood, especially in invertebrates. Using Daphnia magna and its bacterial parasite Pasteuria ramosa as model system, we studied the expression of genes coding for key enzymes in eicosanoid biosynthesis and of genes related to oogenesis in response to dietary arachidonic acid and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…As both ARA and EPA serve as precursors for eicosanoids (Heckmann et al , b ; Schlotz et al ; Garreta‐Lara et al ), they play an important role for Daphnia ’s reproduction and the immune system (Martin‐Creuzburg et al ; Schlotz et al ; Fink and Windisch ). For example, ARA was shown to improve the survival and reproduction of D. magna exposed to an opportunistic bacterial pathogen (Schlotz et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As both ARA and EPA serve as precursors for eicosanoids (Heckmann et al , b ; Schlotz et al ; Garreta‐Lara et al ), they play an important role for Daphnia ’s reproduction and the immune system (Martin‐Creuzburg et al ; Schlotz et al ; Fink and Windisch ). For example, ARA was shown to improve the survival and reproduction of D. magna exposed to an opportunistic bacterial pathogen (Schlotz et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Both ARA and EPA serve as precursors for eicosanoids, a family of hormone-like substances such as prostaglandins, which are known to affect the reproduction, the immune system, and the ion transport physiology of both vertebrates and invertebrates (Stanley-Samuelson 1994;Stanley 2000). Nevertheless, studies investigating the eicosanoid pathway in Daphnia were mostly focused on the role of ARA (Heckmann et al 2008b;Schlotz et al 2012), while the relevance of EPA for the eicosanoid metabolisms was poorly understood until recently (Schlotz et al 2016;Fink and Windisch 2018). The relevance of ARA for Daphnia is further supported by the finding that daphnids accumulate significant amounts of ARA, both during starvation and feeding, either by direct uptake from the diet or by bioconversion of other available ω6-PUFAs (Kainz et al 2004;Schlechtriem et al 2006;Smyntek et al 2008;Burns et al 2011;Taipale et al 2011).…”
mentioning
confidence: 99%
“…Potential pathways for a transformation of the long chain polyunsaturated fatty acid EPA into other endocrine signalling molecules were proposed by [40] and [52], these are: the cyclooxygenase (COx) pathway; 2) the lipoxygenase (LOX) pathway; or 3) the cytochrome P450 pathway. Recent expression studies, however, have shown that COx expression is not affected by EPA-availability [43,51], and so far, no LOX genes have been found in Daphnia species [43]. Overall, our study delivers a profound insight into EPA-connected metabolism, and indicates that a transformation into endocrine signalling may rely on Cytochrome P450-based conversions; these outcomes should be explored in detail by further studies.…”
Section: Cellular Structure and Metabolismmentioning
confidence: 65%
“…The transcriptomic responses so far analysed in connection with long chain polyunsaturated fatty acids rely on studies of enzymes that are involved in eicosanoid synthesis of the "arachidonic pathway" [51]. These enzymes are known to convert eicosanoids into important signalling molecules, such as prostaglandins or leukotrienes in invertebrates, but also in mammals [40,52].…”
Section: Gene Expressionmentioning
confidence: 99%
“…The reverse was true, however, for the second generation where offspring from mothers provided a diet rich in PUFAs produced more eggs but were six-fold more susceptible to the bacterium. Because PUFAs are substrates for hormone-like compounds (eicosanoids) important for both immunity and reproduction, it has been proposed that there is a trade-off between these two functions, particularly when resources are limited (Schlotz et al, 2013(Schlotz et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%